Shelley and the Revolution in taste : the body and the natural world - Morton, Timothy, 1968- (Cambridge University Press, 1994)
"This book brings together the themes of diet, consumption, the body, and human relationships with the natural world, in a highly original study of Shelley. A campaigning vegetarian and proto-ecological thinker, Shelley may seem to us curiously modern, but Morton offers an illuminatingly broad context for Shelley's views in eighteenth-century social and political thought concerning the relationships between humanity and nature. The book is at once grounded in the revolutionary history of the period 1790-1820, and informed by current theoretical issues and anthropological and sociological approaches to literature. Morton provides challenging new readings of much-debated poems, plays, and novels by both Percy and Mary Shelley, as well as the first sustained interpretation of Shelley's prose on diet. With its stimulating literary-historical reassessment of questions about nature and culture, this study will provoke fresh discussion about Shelley, Romanticism, and modernity."--Pub. desc
Keywords: Shelley, Percy Bysshe, -- 1792-1822 -- Political and social views.; Shelley, Percy Bysshe, -- 1792-1822 -- Pensée politique et sociale.; Shelley, Percy Bysshe, -- 1792-1822; Shelley, Percy Bysshe -- 1792-1822; Ernährung.; Shelley, Percy Bysshe.; Human body in literature.; Human-animal relationships -- Public opinion -- History -- 18th century.; Nature conservation -- Public opinion -- History -- 18th century.; Vegetarianism -- Public opinion -- History -- 18th century.; Diet -- Public opinion -- History -- 18th century.; Human-animal relationships in literature.; Vegetarianism in literature.; Nature in literature.; Diet in literature.; Romanticism.; Human Body -- in literature; Diet, Vegetarian -- in literature; Public Opinion; Corps humain dans la littérature.; Relations homme-animal -- Opinion publique -- Histoire -- 18e siècle.; Nature -- Conservation -- Opinion publique -- Histoire -- 18e siècle.; Végétarisme -- Opinion publique -- Histoire -- 18e siècle.; Alimentation -- Opinion publique -- Histoire -- 18e siècle.; Relations humain-animal dans la littérature.; Végétarisme dans la littérature.; Nature dans la littérature.; Alimentation dans la littérature.; Romantisme.; romanticism (form of expression); POETRY -- English, Irish, Scottish, Welsh.; Diet in literature; Diet -- Public opinion; Human-animal relationships in literature; Human-animal relationships -- Public opinion; Human body in literature; Nature conservation -- Public opinion; Nature in literature; Political and social views; Romanticism; Vegetarianism in literature; Körper -- Motiv; Natur -- Motiv; Tiere -- Motiv; Vegetarismus; Geschmack -- Ästhetik; Vegetarisme.; 1700-1799; History